Penerapan Prinsip Universal Design For Learning (UDL) Dalam Kelas Inklusif Peluang Dan Tantangan Di Era Digital - Suwandi; Sindy Sintiya; Rasyidin (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
The application of the universal principle of design for learning (udl) in an inclusive class offers significant opportunities and challenges in the digital age. The study assesses the implementation of udl to meet the needs of various students in an inclusive educational environment. The methods used in this study are qualitative case studies, involving data analysis obtained from interviews and observation. Research results indicate that udl can improve accessibility of learning materials and enrich student learning experiences. However, challenges such as teacher training and proper adoption of technology remain obstacles to its application. These findings provide important insights for educators and policymakers in designing more inclusive learning strategies in the digital age. Universal design for learning (udl) offers a promising approach to creating an inclusive and flexible learning environment for all students. The study analyzes deep application of the udl principle in the context of the digital age inclusive class. Through literature studies and case studies, these studies identify opportunities udl offers, such as increased study motivation, 21st-century skill development, and personalized learning. However, the study also reveals a number of challenges in udl implementation, such as the lack of teacher training, the constraints of technology infrastructure, and resistance